1979
DOI: 10.1099/00221287-113-2-267
|View full text |Cite
|
Sign up to set email alerts
|

Altered Phospholipid Composition in Mutants of Escherichia coli Sensitive or Resistant to Organic Solvents

Abstract: Mutants of Escherichia coli with altered resistance to low molecular weight organic solvents were isolated. Solvent-resistant mutants showed a decrease in the ratio of phosphatidylethanolamine to the anionic phospholipids (phosphatidylglycerol and cardiolipin) relative to the wild-type, whereas solvent-sensitive strains showed an increase. Reversion studies on representative mutants demonstrated that the phenotypic response to solvents and the changes in phospholipid composition were genetically associated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 27 publications
(13 reference statements)
2
25
0
Order By: Relevance
“…All of these responses, both short and long term, result in a less fluid cellular membrane. Regarding phospholipids, the gram-negative organisms P. putida and E. coli have been shown to respond to the presence of toluene by decreasing the membrane content of phosphatidylethanolamine and increasing the content of phosphatidylglycerol and diphosphatidylglycerol, also known as cardiolipin (4,20). After toluene addition, 90% of the de novo phospholipid synthesis is diphosphatidylglycerol synthesis (23).…”
Section: Discussionmentioning
confidence: 99%
“…All of these responses, both short and long term, result in a less fluid cellular membrane. Regarding phospholipids, the gram-negative organisms P. putida and E. coli have been shown to respond to the presence of toluene by decreasing the membrane content of phosphatidylethanolamine and increasing the content of phosphatidylglycerol and diphosphatidylglycerol, also known as cardiolipin (4,20). After toluene addition, 90% of the de novo phospholipid synthesis is diphosphatidylglycerol synthesis (23).…”
Section: Discussionmentioning
confidence: 99%
“…Mueller-Hinton agar was used for MIC determination. The initial inoculum was 10 5 CFU/ml. The activities of ceftazidime, cefepime, ceftriaxone, and cefoperazone against a panel of ␤-lactamase-producing strains were determined alone and in combination at either a 1:1 (ceftazidime) or 2:1 (all agents) ratio with AM-112.…”
mentioning
confidence: 99%
“…On this basis, it stands to reason that cells with an increased content of PI, as in the case of opi1, would have a higher resistance to ethanol. Additionally, altering the ratio of charged head groups has been discussed as a possible mechanism for increased ethanol tolerance 16 . Since PI is the major anionic phospholipid in yeast, it is possible that alterations in membrane charge are responsible for the increased tolerance in PI-enriched cells.…”
Section: Growth Curve Assaysmentioning
confidence: 99%
“…It has been suggested that altering the ratio of charged head groups can affect ethanol tolerance. Clark and Beard 16 found that decreasing the ratio of anionic-to-zwitterionic phospholipids in E. coli, by increasing PE content, rendered yeasts cells less tolerant to organic solvents. Additional reports find reduced ATPase inhibition by ethanol in cells containing higher proportions of PS 9 or PI 12 .…”
Section: Introductionmentioning
confidence: 99%